Management of children and young people with idiopathic pituitary stalk thickening, central diabetes insipidus, or both: a national clinical practice consensus guideline. (September 2021) - Cerbone, Manuela; Visser, Johannes; Bulwer, Chloe; Ederies, Ashraf; Vallabhaneni, Kirtana; Ball, Stephen; Kamaly-Asl, Ian; Grossman, Ashley; Gleeson, Helena; Korbonits, Márta; Nanduri, Vasanta; Tziaferi, Vaya; et al.
Summary: Unexplained or idiopathic pituitary stalk thickening or central diabetes insipidus not only harbours rare occult malignancies in 40% of cases but can also reflect benign congenital defects. Between 2014 and 2019, a multidisciplinary, expert national guideline development group in the UK systematically developed a management flowchart and clinical practice guideline to inform specialist care and improve outcomes in children and young people (aged <19 years) with idiopathic pituitary stalk thickening, central diabetes insipidus, or both. All such cases of idiopathic pituitary stalk thickening and central diabetes insipidus require dynamic pituitary function testing, specialist pituitary imaging, measurement of serum β-human chorionic gonadotropin and alpha-fetoprotein concentrations, chest x-ray, abdominal ultrasonography, optometry, and skeletal survey for occult disease. Stalk thickening of 4 mm or more at the optic chiasm, 3 mm or more at pituitary insertion, or both, is potentially pathological, particularly if an endocrinopathy or visual impairment coexists. In this guideline, we define the role of surveillance, cerebrospinal fluid tumour markers, whole-body imaging, indications, timing and risks of stalk biopsy, and criteria for discharge. We encourage a registry of outcomes to validate the systematic approach described in this guideline and research to establish typical paediatric stalk sizes and the possible role of novel biomarkers, imaging techniques, or both, in diagnosis.